Physicochemical and biochemical spatiotemporal maps of a mouse penis. (5th March 2020) - Hennefarth, Matthew R.; Chen, Ling; Wang, Bohan; Lue, Tom F.; Stoller, Marshall L.; Lin, Guiting; Kang, Misun; Ho, Sunita P.
Abstract: Spatiotemporal mechanobiology resulting in penile pathologies continues to be investigated using small scale animals models such as mice. However, species-dependent functional biomechanics of a mouse penis, is not known. In this study, spatial mapping of a mechanosensitive transcription factor, scleraxis (Scx), at ages 4, 5, 6 weeks, and 1 year were generated to identify mechanoactive regions within penile tissues. Reconstructed volumes of baculum collected using micro X-ray computed tomography illustrated significantly increased baculum length with decreased porosity, and increased mineral density (p < 0.05) with age. The bony-baculum was held centrally in the Scx positive corpus cavernosum glandis (CCG), indicating mechanoactivity within the struts in a 6 week old mouse. The struts also were stained positive for fibrillar proteins including collagen and elastin, and globular proteins including protein gene product 9.5, and α -smooth muscle actin. The corpus cavernosum penis (CCP) contained significantly (p < 0.05) more collagen than CCG within the same penis, and both regions contained blood vessels with equivalent innervation at any given age. Comparison of volumes of flaccid and erect penile forms revealed functional characteristics of the CCP. Results of this study provided insights into biomechanical function of the CCG; in that, it is a high-pressure chamber that stiffens the penis and is similar to the human corpus cavernosum.